2013
DOI: 10.5007/1980-0037.2014v16n1p58
|View full text |Cite
|
Sign up to set email alerts
|

Percepção da imagem corporal em mulheres: prevalência e associação com indicadores antropométricos.

Abstract: The aim of this study was to investigate the prevalence of body image perception and its association with anthropometric indicators (body mass index, waist circumference, waist-height ratio, and conicity index) in women undergoing cervical cancer screening at an institution in Florianópolis, Santa Catarina. The study included 736 women (≥ 18 years). Anthropometric variables (weight, height, waist circumference) were collected for the determination of body mass index, waist-height ratio, and conicity index. Bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…[34][35][36] It has also a negative association with body image satisfaction. 37 The results of the current study showed a negative significant association between WHtR and body image score. Unfortunately, there are few studies which have assessed the association of body image and WHtR, specifically among athletes.…”
Section: Discussionsupporting
confidence: 45%
“…[34][35][36] It has also a negative association with body image satisfaction. 37 The results of the current study showed a negative significant association between WHtR and body image score. Unfortunately, there are few studies which have assessed the association of body image and WHtR, specifically among athletes.…”
Section: Discussionsupporting
confidence: 45%
“…Expectations regarding the ideal female body size and shape have varied across time and culture. In modern Western society the ideal female body typically involves forms of thinness that might range from toned and athletic to slim and lanky (Pelegrini, et al, 2014). The current privileging of the thin female body could possess important ramifications for millennial women.…”
Section: Female Body Imagementioning
confidence: 99%
“…BMI cannot, however, be interpreted as indicative of overall body health because it does not account for a person's percentage of lean and fatty body mass. This limitation is important because current cultural norms of body beauty tend to privilege thinness (Pelegrini, et al, 2014). Recent social movements, such as the fat acceptance movement, have sought to disrupt the anti-fat discourse that can provoke forms of body-based shaming and discrimination (see Cooper, 2010).…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…Extending these observations, other authors [ 50 ] link differences in body satisfaction perception to conditions like eating disorders or psychiatric patterns. In agreement with these observations, some studies [ 51 ] emphasize the importance of educating on the emotional management of body satisfaction perception to prevent dissatisfaction. Such dissatisfaction could lead to diseases associated with being overweight, including cancer or diabetes.…”
Section: Discussionmentioning
confidence: 59%